Krajobraz kulturowy wrocławskiego osiedla Nowy Dwór - Miściorak, Albert (Studia Etnologiczne i Antropologiczne, 2013)
The article treats about a cultural landscape of the Nowy Dwór housing estate in Wrocław. Since its formation in 1938, the very estate has undergone deep topographic and ideologic changes: from the “racially elite” community at the time of national socialism, an “industrial colony” in socialism to the tower block it is nowadays. The aim of considerations on the past and present landscape of the housing estate is to understand the co-relations happening between people and the place of their inhabitance as a cultural phenomenon, and including it in a broader trend of cultural studies dealing with the places of memory, collective memory and cultural landscape.